Student Perceptions of Learner-Centered Teaching - DeDe Wohlfarth; Daniel Sheras; Jessica L. Bennett; Bethany Simon; Jody H. Pimentel; Laura E. Gabel (Park University, 2008)
The learner-centered paradigm departs from traditional teaching models by focusing on students more than teachers and learning more than teaching. Thus, classes are more egalitarian; they emphasize critical thinking, active learning, and real-world assignments. Graduate students in learner-centered classrooms were surveyed about perceptions of their experiences in relation to key dimensions of the learner-centered paradigm and noted that the approach contributed to their felling respected as learners, developed their critical thinking skills, and encouraged their self-directedness. Based on these findings, post-secondary instructors are encouraged to experiment with learning-centered approaches to further explore this promising model.